Diffusion heterogeneity and anisotropy in rat hippocampus - Mazel, T; Simonová, Z; Syková, E (Neuroreport, 1998)
We provide evidence for anisotropic diffusion in rat corpus callosum and hippocampus. The preferential diffusion pathway in corpus callosum is along the myelinated axon fibres; in the hippocampus diffusion is easier along the transversal axis (x) than along the sagittal (y) or vertical (z) axes. In all areas studied, i.e. in the cortex, corpus callosum and hippocampus, the mean ECS volume fraction alpha (alpha = ECS volume/total tissue volume) ranged between 0.20 and 0.22 and mean non-specific uptake k' was between 4.0 and 5.9 x 10(-3) s-1. Diffusional anisotropy in the hippocampus may be of importance for extrasynaptic transmission and in the 'cross-talk' between synapses.
Keywords: Anisotropy; Male; Rats, Wistar; corpus callosum; Diffusion; Iontophoresis; Pyramidal Cells; difuze; pyramidové buňky; mužské pohlaví; potkani Wistar; nervová vlákna; Nerve Fibers; kvartérní amoniové sloučeniny; krysa rodu Rattus; axony; Hippocampus; Animals; Quaternary Ammonium Compounds; extracelulární prostor; Extracellular Space; anizotropie; zvířata; Rats; Corpus Callosum; iontoforéza; Axons; hipokampus